The Extraction of the Density of States of Atomic-Layer-Deposited ZnO Transistors by Analyzing Gate-Dependent Field-Effect Mobility - Minho Yoon (Electronic Materials)
In this study, we investigated the density of states extraction method for atomic-deposited ZnO thin-film transistors (TFTs) by analyzing gate-dependent field-effect mobility. The atomic layer deposition (ALD) method offers ultra-thin and smooth ZnO films, but these films suffer from interface and semiconductor defects, which lead to disordered localized electronic structures. Hence, to investigate the unstable localized structure of ZnO TFTs, we tried to derive the electronic state relationship by assuming field-effect mobility can be expressed as a gate-dependent Arrhenius relation, and the activation energy in the relation is the required energy for hopping. Following this derived relationship, the DOS of the atomic-deposited ZnO transistor was extracted and found to be consistent with those using temperature-dependent measurements. Moreover, to ensure the proposed method is reliable, we applied methods for the extraction of DOSs of doped ZnO transistors, which show enhanced mobilities with shifted threshold voltages, and the results show that the extraction method is reliable. Thus, we can state that the mobility-based DOS extraction method offers practical benefits for estimating the density of states of disordered transistors using a single transfer characteristic of these devices.